2016
DOI: 10.1080/00498254.2016.1185195
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of magnesium isoglycyrrhizinate on the disposition of docetaxel in docetaxel-induced liver injury

Abstract: 1. Magnesium isoglycyrrhizinate (MgIg) has been extensively used in treating liver injury which is the common adverse reaction of docetaxel (DOC). Due to the narrow therapeutic window, small changes in pharmacokinetic profiles can alter the toxicity and therapeutic efficacy of DOC significantly. The study aimed to explore the effects of MgIg on the disposition of DOC and the potential mechanism in DOC-induced liver injury. 2. Pharmacokinetics and tissues distribution behaviors showed that there was no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…GL mainly inhibits the expression of nuclear factor kappa-B (NF-κB) pathway, thereupon then restraining the encoding of important genes such as inflammatory cytokines, anti-apoptotic factors and cyclooxygenase-2 (COX2) ( Li S. et al, 2014 ), achieving anti-inflammatory and anti-tumor effects. Thus, GL is commonly used in treating various cancers in clinical practice ( Stecanella et al, 2021 ; Zuo et al, 2022 ), as well as in alleviating liver, lung, and kidney damage caused by cancer chemotherapy ( Orazizadeh et al, 2014 ; Qu et al, 2017 ). Meanwhile, it also has a protective effect on brain tissue in cases of global cerebral ischemia, brain injury caused by cerebral hemorrhage, and focal ischemia ( Xiong et al, 2016 ).…”
Section: Glycyrrhizic Acidmentioning
confidence: 99%
“…GL mainly inhibits the expression of nuclear factor kappa-B (NF-κB) pathway, thereupon then restraining the encoding of important genes such as inflammatory cytokines, anti-apoptotic factors and cyclooxygenase-2 (COX2) ( Li S. et al, 2014 ), achieving anti-inflammatory and anti-tumor effects. Thus, GL is commonly used in treating various cancers in clinical practice ( Stecanella et al, 2021 ; Zuo et al, 2022 ), as well as in alleviating liver, lung, and kidney damage caused by cancer chemotherapy ( Orazizadeh et al, 2014 ; Qu et al, 2017 ). Meanwhile, it also has a protective effect on brain tissue in cases of global cerebral ischemia, brain injury caused by cerebral hemorrhage, and focal ischemia ( Xiong et al, 2016 ).…”
Section: Glycyrrhizic Acidmentioning
confidence: 99%
“…Its mechanism of action in humans remains to be fully elucidated, however, scavenging of free radicals, prevention of the increase of serum transaminase, reduction of hepatocyte degeneration, necrosis and inflammatory cell infiltration might be included (Wang et al, 2019;Niu et al, 2021). Previous research has shown that MgIG has antiinflammatory, antioxidant, and hepatoprotective activity in toxin-associated liver injury and hepatitis (Jiang et al, 2017a;Qu et al, 2017;Zou et al, 2018). Experimental studies in rodents demonstrated protective action against methotrexate, cyclophosphamide, paclitaxel, lipopolysaccharide, concanavalin A, ethanol, and free fatty acid (Cheng et al, 2009;Chen et al, 2014;Yang et al, 2016;Jiang et al, 2017a;Jiang et al, 2017b;Lu et al, 2017;Cao et al, 2019).…”
Section: Magnesium Isoglycyrrhizinatementioning
confidence: 99%
“…SIRT1, an inhibitory transcriptional factor for the NLRP3 inflammasome, is reported to act as a protective mediator for DILI [ 14 ]. Docetaxel, a chemotherapeutic drug widely applied for the treatment of malignant tumors, is reported to induce severe liver injury during clinical treatments [ 15 , 16 ]. It is of great significance to develop effective therapies for the DILI during the Docetaxel treatments.…”
Section: Introductionmentioning
confidence: 99%